Respuesta :

Answer:

x = 2, x = 8

Step-by-step explanation:

reminder that f'(x) = [tex]m_{tangent}[/tex]

Differentiate f(x) term by term using the power rule

[tex]\frac{d}{dx}[/tex] (a[tex]x^{n}[/tex] )  = na[tex]x^{n-1}[/tex]

f(x) = [tex]\frac{1}{3}[/tex] x³ - 5x² + 2x + 10

f'(x) = x² - 10x + 2

Equating f'(x) to - 14

x² - 10x + 2 = - 14 ( add 14 to both sides )

x² - 10x + 16 = 0 ← in standard form

(x - 2)(x - 8) = 0 ← in factored form

Equate each factor to zero and solve for x

x - 2 = 0 ⇒ x = 2

x - 8 = 0 ⇒ x = 8